Metodologia de inspeção em estruturas de pontes de concreto armado - Euqueres, Priscilla (2011)
The objective this work is to develop and implement a methodology for special inspection on Concrete Bridges trough the quantitative analysis of the degree of deterioration of the structures so that it can serve as a basis for making decisions related to the rehabilitation of these structures. In order to develop and apply the methodology on concrete bridges, the existing methods of inspection of concrete structures were studied and adapted to the adapting to the concrete bridges. The methodology was based on GDE/UnB model in their latest formulation (Fonseca,2007) and adapted to the tables with the elements to be analyzed, together with the pathological manifestations that can occur in each element, timing and interventions classification of the level of deterioration and the relevant factors to each family of concrete bridges. A pilot study was proposed to validate the methodology. Results showed that there was a need for further adaptation, to consider the caculations of the degree of deterioration of both the family or the. With the changes proposed in the pilot study were made over 11 (eleven) inspections in order to validate the proposed methodology. With the results obtained it was concluded that the methodology for inspection of bridges is valid and of great importance to public organisms and surveyors to make decisions about the best time and the best item to be rehabilitated, being a single element, as a family elements, or the structure as a whole. One downside is that the methodoly for bridges with lenght greater than 70 meters most be used with caution, because the median openings are difficult to visual assessment. However the methodology can be used in order to obtain basic understanding of the visible elements, and after the intervention, we can make another more detailed analysis using not only the elements of routine inspection as binoculars, measuring tape, camera, among others, but also nautical elements, which provide the best viewing responsible for the inspection of the median elements